Survival and Control of Campylobacter in Poultry Production Environment - Hakeem, Mohammed J. (Front Cell Infect Microbiol, 2021)
Campylobacter species are Gram-negative, motile, and non–spore-forming bacteria with a unique helical shape that changes to filamentous or coccoid as an adaptive response to environmental stresses. The relatively small genome (1.6 Mbp) of Campylobacter with unique cellular and molecular physiology is only understood to a limited extent. The overall strict requirement of this fastidious microorganism to be either isolated or cultivated in the laboratory settings make itself to appear as a weak survivor and/or an easy target to be inactivated in the surrounding environment of poultry farms, such as soil, water source, dust, surfaces and air. The survival of this obligate microaerobic bacterium from poultry farms to slaughterhouses and the final poultry products indicates that Campylobacter has several adaptive responses and/or environmental niches throughout the poultry production chain. Many of these adaptive responses remain puzzles. No single control method is yet known to fully address Campylobacter contamination in the poultry industry and new intervention strategies are required. The aim of this review article is to discuss the transmission, survival, and adaptation of Campylobacter species in the poultry production environments. Some approved and novel control methods against Campylobacter species throughout the poultry production chain will also be discussed.